Dogs, Past and Present An Interdisciplinary Perspective - Fiore, Ivana; Lugli, Francesca (2023)
Dogs, Past and Present: An Interdisciplinary Perspective contributions from scholars from a variety of disciplines to provide a comprehensive assessment of the importance of dogs through history. Over the last decades, countless studies have examined the lives of dogs and their current place in our societies as well as their crucial part in human life and history. Data and hypotheses have progressively increased, sometimes controversially, in each field of investigation. The domestication of dogs and its success during prehistory is a fascinating theme that scholars of various disciplines are involved with. However, there has not been a real exchange between those approaches and it is extremely complex to reach a complete view of the thousands of texts which are published every year. By contrast, this volume is entirely dedicated to dogs and it is focused on the necessity of an 'interdisciplinary perspective' to fully understand the fundamental role that dogs have played in our past. When, where, how and why were dogs domesticated? What is their story? What was their role in the history of humankind? What is their role in traditional and non-traditional societies today? The book originated from the conference 'Dogs, Past and Present - an Interdisciplinary Perspective' held at CNR (National Scientific Council) and at Sapienza University in Rome (14-17 November 2018), promoted by the Italian Association for Ethnoarchaeology and organised by the editors.